Who's missing in the group? Argument sharing in core cosubordinate construction in Filipino - Bazar, Aquiles P. (Animo Repository, 2008)
This paper examines the relationship between two important arguments in core cosubordinate construction in Filipino: namely, controller found in the matrix core and the missing argument (controllee) in the linked core using the framework Role and Reference Grammar of Van Valin (2005). This paper has proved that there is really an argument sharing between two cores and each core plays a crucial role in the syntactic development of cosubordinate clauses. The first core assigns the juncture levels and nexus of relations of the units involved, whereas the second core determines the syntactic structure of the clause. The researcher also found out that regardless of the number of arguments found in the linked core, the matrix core argument which is also the controller is the same with the missing actor argument from the linked core. © 2008 - Aquiles P. Bazar III.